Evaluating AAL Systems Through Competitive Benchmarking. Indoor Localization and Tracking International Competition, EvAAL 2011, Competition in Valencia, Spain, July 25-29, 2011, and Final Workshop in Lecce, Italy, September 26, 2011. Revised Selected Papers - Chessa, Stefano; Knauth, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the international competition aimed at the evaluation and assessment of Ambient Assisted Living (AAL) systems and services, EvAAL 2011, which was organized in two major events, the Competition in Valencia, Spain, in July 2011, and the Final workshop in Lecce, Italy, in September 2011. The papers included in this book describe the organization and technical aspects of the competition, and provide a complete technical description of the competing artefacts and report on the experience lessons learned by the teams during the competition.
Organization and technical aspects of the competition -- Technical description of the competing artefacts -- Experience lessons learned by the teams during the competition.
Keywords: Computer science; Operating systems (Computers).; Software engineering; Computer system performance; Computer Science; System Performance and Evaluation; Special Purpose and Application-Based Systems; Performance and Reliability; Computers and Society; Information Systems Applications (incl. Internet).; Computer Applications